Role of osteocytes in bone response to mechanical loading - Khalid, Kamarul Ariffin; Findlay, David M.; Atkins, Gerald J (2010)
Much interest has been generated in investigating what effect mechanical stimuli have on bone and bone remodeling. Most published reports are pointing towards the central role that osteocytes have in what is now known as a very dynamic and adaptive biological response. In 2003 a report was published concerning the development of a novel device (ZetOS(TM)) that enables the long-term culture of cancellous bone, with the application of specific and measureable mechanical loading and the precise measurement of the resultant strain.